Assessment of maternal and foetal outcome in elderly primigravida: a prospective observational study - Devi, Pothula Sudheshna; Sachdev, Rakhi; Shishodiya, Madhu; Bhadouriya, Amrita S.; Basu, Rakhi; Hussain, Roshan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: An elderly primigravida means age more than 35 years. Several maternal and foetal risk factors are well-established in elderly primigravida mothers. The study aimed to evaluate the maternal and foetal outcome in elderly primigravida mothers of central part of India and also to identify risks associated with advanced maternal age for mother. Methods: The study was conducted as an observational prospective study in Jawaharlal Nehru Hospital and Research Centre, Bhilai, Chhattisgarh. In this study, the 82 mothers presenting primigravida aged ≥35 years and attending antenatal clinic for the period of January 2019 to December 2020. All primigravida aged 35 years and above, attending antenatal clinic, all primigravida aged 35 years and above admitted in emergency. We used data for demographic and socioeconomic status of the subjects, various obstetrics parameters related to gestational period and other relevant data were collected at the time of registration and the subjects were followed up till delivery and discharge. Detailed maternal and foetal outcomes were recorded. Results: In the present study, the mean age was of about 36.52±2.41 years among the studied mothers. Higher education and socioeconomic status revealed the conception for pregnancy was found to be delayed. This concept is leading to more LSCS following antenatal complications of mothers that may be causative factors for neonatal complications. In the present study, no mortality was observed among newborns. Conclusions: It was concluded that vaginal deliveries were significantly less and there was an increase in caesarean section rate in this study. Management will largely depend on attempts at improving perinatal outcome without compromise to health and well-being of the mother.